Perception of Oncology Patients toward the Quality of Life and Rehabilitation: Perception of Oncology Patients - Jamil, Komal; Baqir, Syeda Rida; Tasneem Chaudhary, Sharjeel; Sandeela, Khadijatul Ain; Iqbal, Rasheed; Aslam, Shafaq (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2023)
Cancer is a worldwide pandemic disease 1 in 8 deaths is due to cancer globally. The major parameter used for the evaluation of cancer treatment is quality of life. Objective: To find out the perception of oncology patients towards the quality of life and rehabilitation. Methods: This study was a cross-sectional survey conducted in two tertiary care hospitals and one medical center in Karachi. Non-probability purposive sampling technique was used for sampling. Ethical approval was prior obtained from Parent Institute. Data were analyzed by SPSS version-23.0. Result: A total of 255 survey forms were filled out by oncology patients. Mostly158 (62.0%) patients lie between the ages of 20-49 years. There were 117 (45.9%) males and 138 (54.1%) females. Change in quality of life with time related to post-diagnosis. Those who were diagnosed < 5 years rated mean overall physical health as 5.46 ± 1.7, > 10 years rated 4.39 ± 1.8, and 5-10 years rated 4.22 ± 1.5. Satisfaction of patients regarding physical therapy sessions <5 years of post-diagnosed responded mean satisfaction level was 7.33 ± 2.494, 5.00 ± 1.633 of >10 years patients, and 6.08 ± 1.714 of 5 to 10 years post diagnosed patients. Improvement in QOL after physical therapy sessions <5 years diagnosed patients responded mean QOL as 7.39 ± 2.367, >10 years of patients responded 5.70 ± 2.032, and 5 to 10 years patients responded 6.45 ± 1.670. Conclusions: This study concluded that the perception of oncology patients regarding rehabilitation to maintain their quality of life is significant.